Low-temperature graphite negative electrode material and preparation method thereof

By oxidizing the graphite negative electrode material and synthesis of molybdenum disulfide-graphite composite, and coated with amorphous resin carbon/nickel oxide and polythiophene film, the problem of degradation of graphite negative electrode material in low temperature environment is solved, and efficient Lithium ion transport and good cycling stability.

CN119430310AInactive Publication Date: 2025-02-14青岛青北碳素制品有限公司

Patent Information

Application Number
CN202411612288.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In a low temperature environment, the impedance of the solid electrolyte interface film of the surface of the graphite negative electrode material increases, resulting in a decrease in the lithium ion transmission rate and the battery cannot charge and discharge normally, affecting the battery capacity retention rate and cycling efficiency.

Method used

By mixing materials such as potassium persulfate, phosphorus pentoxide, graphite sheets, etc., oxidation treatment and synthesis of molybdenum disulfide-graphite composites, the amorphous resin carbon/nickel oxide and polythiophene film are further coated to enhance the conductivity of the material. and cycle stability.

Benefits of technology

The ion diffusion efficiency and rate performance of low-temperature graphite anode materials are improved, cycle stability and electrochemical lithium storage performance are enhanced, and the battery maintains efficient operation over a wider temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a low-temperature graphite negative electrode material and a preparation method thereof, and belongs to the technical field of high polymer materials. According to the prepared low-temperature graphite negative electrode material, firstly, the surface of graphite is pre-oxidized through potassium persulfate, phosphorus pentoxide and concentrated sulfuric acid, and then under the action of sodium nitrate, potassium permanganate and hydrogen peroxide, graphite oxide is prepared; then, ammonium molybdate hydrate and thioacetamide are used as a molybdenum source and a sulfur source, graphite oxide is used as a supporting material, a molybdenum disulfide-graphite compound is synthesized, and the conductivity and the cycling stability are improved; secondly, the surface of the negative electrode is coated with amorphous resin carbon / nickel oxide, so that the ion diffusion efficiency of the low-temperature graphite negative electrode material is enhanced, and the electrochemical lithium storage performance is improved in a low-temperature environment; and finally, the surface of the amorphous resin carbon / nickel oxide is coated with a layer of polythiophene film, so that the rate capability of the negative electrode material is improved due to large surface area and high pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a low-temperature graphite negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have shown broad application prospects in energy storage systems, transportation and portable devices due to their high open circuit potential, high energy density, excellent cycle performance and no memory effect. At present, graphite is still the preferred negative electrode material for lithium-ion batteries due to its stable discharge platform, long cycle life and low price. However, graphite has a low working potential and is easily affected by polarization. Especially in low temperature environments, the impedance of the solid electrolyte interface film on its surface increases sharply, significantly slowing down the lithium ion transmission rate, resulting in the battery being unable to charge and discharge normally.

[0003] Under low temperature environment, the performance of graphite negative electrode materials declines significantly, the ion migration rate decreases, diffusion is hindered, and polarization intensifies, resulting in reduced battery capacity, weakened charge and discharge efficiency, and even failure. It not only affects the battery's capacity retention rate and cycle efficiency, but also shortens the equipment's operating time and affects the user experience. Therefore, the development of graphite negative electrode materials suitable for low temperatures has important research significance and practical application value. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a low-temperature graphite negative electrode material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a low-temperature graphite negative electrode material specifically comprises the following steps: Step A1: potassium persulfate, phosphorus pentoxide, graphite flakes and concentrated sulfuric acid are mixed evenly, stirred at a constant temperature of 80°C for 6 hours, then sodium nitrate is added, stirred in an ice bath for 0.5 hours, the temperature is raised to 15°C, potassium permanganate is added, stirred for 0.5 hours, the temperature is raised to 35°C, stirred for 3 hours, the system temperature is raised to 95°C, the temperature is kept constant for 1 hour, then cooled to 60°C, hydrogen peroxide and deionized water are added, the reaction is carried out for 1 hour, centrifugation is performed to wash until neutral, and vacuum drying is carried out at 50°C to obtain graphite oxide; Further, the usage ratio of potassium persulfate, phosphorus pentoxide, graphite flakes, concentrated sulfuric acid, sodium nitrate, potassium permanganate, hydrogen peroxide, and deionized water is 2 g: 1 g: 1-2 g: 20-46 mL: 2-3.75 g: 20 g: 40-50 mL: 100-200 mL; Step A2: disperse graphite oxide in acetone, deionized water and ethanol, perform ultrasonic treatment for 10 min, add hydrated ammonium molybdate and thioacetamide, mix well, stir for 30 min, react at 75 ° C for 9 h, filter, wash, and vacuum dry at 60 ° C for 12 h to obtain MoS2-Gr; Further, the usage ratio of graphite oxide, acetone, deionized water, ethanol, hydrated ammonium molybdate, and thioacetamide is 0.5-0.6 g: 280-320 mL: 50-60 mL: 50-60 mL: 0.7 g: 0.5-0.6 g; Step A3: Disperse epoxy resin in ethanol solution, stir evenly, add MoS2-Gr and nickel oxide, keep in an oven at 180°C for 5 hours for coking treatment, heat treatment at 1000°C at a heating rate of 5°C / min in an argon atmosphere for 2 hours, and cool to room temperature to obtain C / Ni@MoS2-Gr; Further, the usage ratio of epoxy resin, ethanol, MoS2-Gr, and nickel oxide is 0.2-0.3 g: 20-30 mL: 1.8-2.7 g: 0.2-0.3 g; Step A4: Add ammonium persulfate to 50-100 mL of deionized water and mix well, cool in an ice bath for 2 h, and record it as solution A. Add thiophene monomer to 80 mL of deionized water, and ultrasonically disperse it for 30 min. Add C / Ni@MoS2-Gr to 30 mL of deionized water, and ultrasonically disperse it for 30 min. Mix the two and continue ultrasonicating for 30 min. Then slowly drop solution A in an ice water bath. After the dropwise addition, continue stirring the reaction for 2-4 h, centrifuge and wash, and dry to obtain PTh@C / Ni@MoS2-Gr. Further, the dosage ratio of ammonium persulfate, thiophene monomer, C / Ni@MoS2-Gr, and solution A is 34.0-38.0 g: 3.2-3.8 g: 0.031-0.059 g: 10-15 mL; Step A5: PTh@C / Ni@MoS2-Gr is dispersed in a reactor containing N,N-dimethylformamide, ultrasonically dispersed, heated to 55-65°C, mechanically stirred at 80-120rpm, and then tetrahydrofuran is added. The reaction time is 5-6h, and the mixture is allowed to stand for 24h, washed and dried, and heated to 780-820°C and calcined for 6-7h in a nitrogen environment. After cooling, the mixture is dispersed to obtain a low-temperature graphite negative electrode material; Furthermore, the usage ratio of PTh@C / Ni@MoS2-Gr, N,N-dimethylformamide, and tetrahydrofuran is 0.5-2g:60mL:0.8-2.4g.

[0006] Beneficial effects of the present invention: The low-temperature graphite negative electrode material prepared by the present invention comprises the following steps: firstly, pre-oxidizing the graphite surface by using potassium persulfate, phosphorus pentoxide and concentrated sulfuric acid, and then preparing graphite oxide under the action of sodium nitrate, potassium permanganate and hydrogen peroxide; then, synthesizing a molybdenum disulfide-graphite composite by using hydrated ammonium molybdate and thioacetamide as molybdenum sources and sulfur sources and graphite oxide as a supporting material, thereby improving the conductivity and cycle stability; secondly, coating the negative electrode surface with amorphous resin carbon / nickel oxide, thereby enhancing the ion diffusion efficiency of the low-temperature graphite negative electrode material; and finally, coating the surface of the amorphous resin carbon / nickel oxide with a layer of polythiophene film, which has a larger surface area and higher pores, thereby improving the rate performance of the negative electrode material.

[0007] The negative electrode material of the present invention firstly oxidizes the graphite with a loose, porous, interconnected and layered unique structure to increase the specific surface area and the powder compaction density, thereby enhancing the chemical properties of the material; then, a low-temperature solvent thermal method is used to synthesize MoS2-Gr to avoid the large size of the active material caused by high-temperature reaction, improve the structure of the composite material, and enhance its stability. Due to the unique sandwich-like structure of the transition metal sulfide MoS2, it is Li +It provides more active sites during repeated charge and discharge processes. At the same time, the synergistic effect of graphite and MoS2 makes the composite exhibit excellent electrochemical properties. MoS2 is evenly distributed on the graphite surface, which not only shortens the lithium ion diffusion distance and improves the rate performance, but also effectively buffers the volume expansion of MoS2, thereby enhancing the cycle stability; secondly, a layer of amorphous resin carbon and nickel oxide composite coating layer is constructed on the MoS2-Gr surface by a liquid phase coating method. The amorphous carbon layer not only provides more diffusion channels for lithium ions, but also anchors the nickel oxide particles on the graphite surface, strengthening the interface contact. This synergistic coating method improves the ion diffusion efficiency of the graphite composite negative electrode material and improves the electrochemical lithium storage performance of the electrode material at low temperatures; finally, a layer of polythiophene film is coated on the basis of the above-mentioned coating layer, which synergizes with the amorphous resin carbon and nickel oxide composite coating layer to further improve the electrochemical performance of the negative electrode material. Coating effectively reduces the direct contact between the negative electrode material and H2O and CO2 in the atmosphere, reduces the generation of residual lithium on the surface of the negative electrode material, and enhances the interface stability, thereby showing good cycle stability. In addition, polythiophene also has excellent chemical stability. In addition, when preparing low-temperature graphite negative electrode materials, tetrahydrofuran is used as an electrolyte solvent to improve the chemical properties of the electrolyte, enhance the desolvation ability of potassium ions, inhibit the co-embedding of potassium ions and solvents, and improve the cycle stability and energy density of the graphite negative electrode. Its ortho-substituent structure weakens the interaction between potassium ions and solvents, prevents the co-embedding of potassium ions and solvents, and helps to improve the performance of graphite negative electrodes in low temperature environments, allowing them to maintain high efficiency in a wider temperature range. At the same time, the solvation structure of tetrahydrofuran is rich in anions, which is conducive to the formation of a fluoride-rich solid electrolyte interface layer (SEI layer) on graphite, further improving the cycle stability of the graphite negative electrode. DETAILED DESCRIPTION

[0008] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0009] A method for preparing a low-temperature graphite negative electrode material specifically comprises the following steps: Step A1: 2 g potassium persulfate, 1 g phosphorus pentoxide, 1 g graphite flakes and 20 mL concentrated sulfuric acid were mixed evenly, stirred at a constant temperature of 80° C. for 6 h, then 2 g sodium nitrate was added, stirred in an ice bath for 0.5 h, the temperature was raised to 15° C., 20 g potassium permanganate was added, stirred for 0.5 h, the temperature was raised to 35° C., stirred for 3 h, the system temperature was raised to 95° C., the temperature was kept constant for 1 h, then cooled to 60° C., 40 mL hydrogen peroxide and 100 mL deionized water were added, the reaction was carried out for 1 h, centrifuged and washed until neutral, and vacuum dried at 50° C. to obtain graphite oxide; Step A2: 0.5 g of graphite oxide was dispersed in 280 mL of acetone, 50 mL of deionized water and 50 mL of ethanol, and ultrasonically treated for 10 min. Then, 0.7 g of hydrated ammonium molybdate and 0.5 g of thioacetamide were added and mixed evenly. The mixture was stirred for 30 min, reacted at 75 ° C for 9 h, filtered, washed, and vacuum dried at 60 ° C for 12 h to obtain MoS2-Gr; Step A3: 0.2 g of epoxy resin was dispersed in 20 mL of ethanol solution, stirred evenly, 1.8 g of MoS2-Gr and 0.2 g of nickel oxide were added, and the mixture was kept in an oven at 180 ° C for 5 h for coking treatment, and then heated to 1000 ° C at a heating rate of 5 ° C / min in an argon atmosphere for 2 h for heat treatment, and cooled to room temperature to obtain C / Ni@MoS2-Gr; Step A4: Add 34.0g of ammonium persulfate to 50mL of deionized water and mix well, cool in an ice bath for 2h, record as solution A, add 3.2g of thiophene monomer to 80mL of deionized water, ultrasonically disperse for 30min, add 0.031g of C / Ni@MoS2-Gr to 30mL of deionized water, ultrasonically disperse for 30min, mix the two and continue ultrasonication for 30min, then slowly add 10mL of solution A dropwise in an ice bath, continue stirring and reacting for 2h after the addition is completed, centrifuge and wash, and dry to obtain PTh@C / Ni@MoS2-Gr; Step A5: Disperse 0.5g PTh@C / Ni@MoS2-Gr in a reactor containing 60mL N,N-dimethylformamide, ultrasonically disperse, heat to 55°C, mechanically stir at 80rpm, add 0.8g tetrahydrofuran, react for 5h, let stand for 24h, wash and dry, heat to 780°C in a nitrogen environment, and calcine for 6h. After cooling, break up to obtain a low-temperature graphite negative electrode material. Example 2

[0010] A method for preparing a low-temperature graphite negative electrode material specifically comprises the following steps: Step A1: 2 g potassium persulfate, 1 g phosphorus pentoxide, 1.3 g graphite flakes and 28 mL concentrated sulfuric acid were mixed evenly, stirred at a constant temperature of 80° C. for 6 h, then 2.58 g sodium nitrate was added, stirred in an ice bath for 0.5 h, the temperature was raised to 15° C., 20 g potassium permanganate was added, stirred for 0.5 h, the temperature was raised to 35° C., stirred for 3 h, the system temperature was raised to 95° C., the temperature was kept constant for 1 h, then cooled to 60° C., 44 mL hydrogen peroxide and 135 mL deionized water were added, the reaction was carried out for 1 h, centrifuged and washed until neutral, and vacuum dried at 50° C. to obtain graphite oxide; Step A2: 0.53 g of graphite oxide was dispersed in 293 mL of acetone, 53 mL of deionized water and 53 mL of ethanol, and ultrasonically treated for 10 min. Then, 0.7 g of hydrated ammonium molybdate and 0.53 g of thioacetamide were added and mixed evenly. The mixture was stirred for 30 min, reacted at 75 ° C for 9 h, filtered, washed, and vacuum dried at 60 ° C for 12 h to obtain MoS2-Gr; Step A3: 0.23 g of epoxy resin was dispersed in 23 mL of ethanol solution, stirred evenly, 2.1 g of MoS2-Gr and 0.23 g of nickel oxide were added, and the mixture was kept in an oven at 180 ° C for 5 h for coking treatment, and then heated to 1000 ° C at a heating rate of 5 ° C / min in an argon atmosphere for 2 h for heat treatment, and cooled to room temperature to obtain C / Ni@MoS2-Gr; Step A4: Add 35.0g of ammonium persulfate to 65mL of deionized water and mix well, cool in an ice bath for 2h, record as solution A, add 3.4g of thiophene monomer to 80mL of deionized water, ultrasonically disperse for 30min, add 0.040g of C / Ni@MoS2-Gr to 30mL of deionized water, ultrasonically disperse for 30min, mix the two and continue ultrasonication for 30min, then slowly add 11.5mL of solution A dropwise in an ice bath, continue stirring and reacting for 2.5h after the addition is completed, centrifuge and wash, and dry to obtain PTh@C / Ni@MoS2-Gr; Step A5: Disperse 1.25g PTh@C / Ni@MoS2-Gr in a reactor containing 60mL N,N-dimethylformamide, ultrasonically disperse, heat to 58°C, mechanically stir at 96rpm, add 1.3g tetrahydrofuran, react for 5.5h, let stand for 24h, wash and dry, heat to 795°C in a nitrogen environment, calcine for 6.5h, and break up after cooling to obtain a low-temperature graphite negative electrode material. Example 3

[0011] A method for preparing a low-temperature graphite negative electrode material specifically comprises the following steps: Step A1: 2 g potassium persulfate, 1 g phosphorus pentoxide, 1.6 g graphite flakes and 36 mL concentrated sulfuric acid were mixed evenly, stirred at a constant temperature of 80°C for 6 h, then 3.16 g sodium nitrate was added, stirred in an ice bath for 0.5 h, the temperature was raised to 15°C, 20 g potassium permanganate was added, stirred for 0.5 h, the temperature was raised to 35°C, stirred for 3 h, the system temperature was raised to 95°C, the temperature was kept constant for 1 h, then cooled to 60°C, 46 mL hydrogen peroxide and 165 mL deionized water were added, the reaction was carried out for 1 h, centrifuged and washed until neutral, and vacuum dried at 50°C to obtain graphite oxide; Step A2: 0.56 g of graphite oxide was dispersed in 305 mL of acetone, 56 mL of deionized water and 56 mL of ethanol, and ultrasonically treated for 10 min. Then, 0.7 g of hydrated ammonium molybdate and 0.56 g of thioacetamide were added and mixed evenly. The mixture was stirred for 30 min, reacted at 75 ° C for 9 h, filtered, washed, and vacuum dried at 60 ° C for 12 h to obtain MoS2-Gr; Step A3: 0.26 g of epoxy resin was dispersed in 26 mL of ethanol solution, stirred evenly, 2.4 g of MoS2-Gr and 0.26 g of nickel oxide were added, and the mixture was kept in an oven at 180 ° C for 5 h for coking treatment, and then the temperature was raised to 1000 ° C at a heating rate of 5 ° C / min in an argon atmosphere for heat treatment for 2 h, and cooled to room temperature to obtain C / Ni@MoS2-Gr; Step A4: Add 36.5g of ammonium persulfate to 85mL of deionized water and mix well, cool in an ice bath for 2h, record as solution A, add 3.6g of thiophene monomer to 80mL of deionized water, ultrasonically disperse for 30min, add 0.050g of C / Ni@MoS2-Gr to 30mL of deionized water, ultrasonically disperse for 30min, mix the two and continue ultrasonication for 30min, then slowly add 13.5mL of solution A dropwise in an ice water bath, continue stirring and reacting for 3.5h after the addition is completed, centrifuge and wash, and dry to obtain PTh@C / Ni@MoS2-Gr; Step A5: Disperse 1.25g PTh@C / Ni@MoS2-Gr in a reactor containing 60mL N,N-dimethylformamide, ultrasonically disperse, heat to 62°C, mechanically stir at 112rpm, add 1.9g tetrahydrofuran, react for 5.5h, let stand for 24h, wash and dry, heat to 805°C in a nitrogen environment, calcine for 6.5h, and break up after cooling to obtain a low-temperature graphite negative electrode material. Example 4

[0012] A method for preparing a low-temperature graphite negative electrode material specifically comprises the following steps: Step A1: 2 g potassium persulfate, 1 g phosphorus pentoxide, 2 g graphite flakes and 46 mL concentrated sulfuric acid were mixed evenly, stirred at a constant temperature of 80° C. for 6 h, then 3.75 g sodium nitrate was added, stirred in an ice bath for 0.5 h, the temperature was raised to 15° C., 20 g potassium permanganate was added, stirred for 0.5 h, the temperature was raised to 35° C., stirred for 3 h, the system temperature was raised to 95° C., the temperature was kept constant for 1 h, then cooled to 60° C., 50 mL hydrogen peroxide and 200 mL deionized water were added, the reaction was carried out for 1 h, centrifuged and washed until neutral, and vacuum dried at 50° C. to obtain graphite oxide; Step A2: 0.6 g of graphite oxide was dispersed in 320 mL of acetone, 60 mL of deionized water and 60 mL of ethanol, and ultrasonically treated for 10 min. Then, 0.7 g of hydrated ammonium molybdate and 0.6 g of thioacetamide were added and mixed evenly. The mixture was stirred for 30 min, reacted at 75 ° C for 9 h, filtered, washed, and vacuum dried at 60 ° C for 12 h to obtain MoS2-Gr; Step A3: 0.3 g of epoxy resin was dispersed in 30 mL of ethanol solution, stirred evenly, 2.7 g of MoS2-Gr and 0.3 g of nickel oxide were added, and the mixture was kept in an oven at 180 ° C for 5 h for coking treatment, and then the temperature was raised to 1000 ° C at a heating rate of 5 ° C / min in an argon atmosphere for heat treatment for 2 h, and then cooled to room temperature to obtain C / Ni@MoS2-Gr; Step A4: Add 38.0g of ammonium persulfate to 100mL of deionized water and mix well, cool in an ice bath for 2h, record as solution A, add 3.8g of thiophene monomer to 80mL of deionized water, ultrasonically disperse for 30min, add 0.059g of C / Ni@MoS2-Gr to 30mL of deionized water, ultrasonically disperse for 30min, mix the two and continue ultrasonication for 30min, then slowly add 15mL of solution A dropwise in an ice water bath, continue stirring and reacting for 4h after the addition is completed, centrifuge and wash, and dry to obtain PTh@C / Ni@MoS2-Gr; Step A5: Disperse 2g PTh@C / Ni@MoS2-Gr in a reactor containing 60mL N,N-dimethylformamide, ultrasonically disperse, heat to 65°C, mechanically stir at 120rpm, add 2.4g tetrahydrofuran, react for 6h, let stand for 24h, wash and dry, heat to 820°C in a nitrogen environment, and calcine for 7h. After cooling, break up to obtain a low-temperature graphite negative electrode material.

[0013] Comparative Example 1 This comparative example is a low-temperature graphite negative electrode material. The difference from Example 3 is that hydrated ammonium molybdate and thioacetamide as molybdenum source and sulfur source are not added to the negative electrode material, and the rest are the same.

[0014] Comparative Example 2 This comparative example is a low-temperature graphite negative electrode material. The difference from Example 3 is that the surface of the negative electrode material is not coated with a composite coating layer of amorphous resin carbon and nickel oxide, and the rest is the same.

[0015] Performance test: The low-temperature graphite negative electrode material prepared in Example 1-4 and Comparative Example 1-2 and PVDF were mixed in a mass ratio of 9:1, and N-methylpyrrolidone was added to homogenize the mixture. The solid content was 55%, and a slurry was prepared. The copper foil was used as the negative electrode collector, and the slurry was scraped on the surface of the copper foil by a scraping method. The scraping amount was 30 mg / cm 2 , placed in a vacuum drying oven at 120℃ for 24h, cut into negative electrode sheets, and the prepared negative electrode sheets were used in the negative electrode of CR2025 button batteries. The charge and discharge tests were carried out at a rate of 0.2C using a CT2001-A battery tester. The lithium insertion specific capacity was tested at temperatures of 25℃, 0℃, -10℃ and -20℃. The system was charged and discharged at a constant current with a voltage of 0.01-3.0V to test the cycle capacity retention rate. The test results are shown in the following table:

[0016] It can be seen from the test data in the table that the low-temperature graphite negative electrode material prepared in Example 1 not only has excellent cycle performance, can improve the electrochemical lithium storage performance under low temperature environment, but also has good rate performance.

[0017] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a low-temperature graphite negative electrode material, characterized in that: The specific steps include: Step A1: potassium persulfate, phosphorus pentoxide, graphite flakes and concentrated sulfuric acid are mixed evenly, stirred at a constant temperature of 80°C for 6 hours, then sodium nitrate is added, stirred in an ice bath for 0.5 hours, the temperature is raised to 15°C, potassium permanganate is added, stirred for 0.5 hours, the temperature is raised to 35°C, stirred for 3 hours, the system temperature is raised to 95°C, the temperature is kept constant for 1 hour, then cooled to 60°C, hydrogen peroxide and deionized water are added, the reaction is carried out for 1 hour, centrifugation is performed to wash until neutral, and vacuum drying is carried out at 50°C to obtain graphite oxide; Step A2: disperse graphite oxide in acetone, deionized water and ethanol, perform ultrasonic treatment for 10 min, add hydrated ammonium molybdate and thioacetamide, mix well, stir for 30 min, react at 75 ° C for 9 h, filter, wash, and vacuum dry at 60 ° C for 12 h to obtain MoS2-Gr; Step A3: Disperse epoxy resin in ethanol solution, stir evenly, add MoS2-Gr and nickel oxide, keep in an oven at 180°C for 5 hours for coking treatment, heat treatment at 1000°C at a heating rate of 5°C / min in an argon atmosphere for 2 hours, and cool to room temperature to obtain C / Ni@MoS2-Gr; Step A4: Add ammonium persulfate to 50-100 mL of deionized water and mix well, cool in an ice bath for 2 h, and record it as solution A. Add thiophene monomer to 80 mL of deionized water, and ultrasonically disperse it for 30 min. Add C / Ni@MoS2-Gr to 30 mL of deionized water, and ultrasonically disperse it for 30 min. Mix the two and continue ultrasonicating for 30 min. Then slowly drop solution A in an ice water bath. After the dropwise addition, continue stirring the reaction for 2-4 h, centrifuge and wash, and dry to obtain PTh@C / Ni@MoS2-Gr. Step A5: Disperse PTh@C / Ni@MoS2-Gr in a reactor containing N,N-dimethylformamide, perform ultrasonic dispersion, heat to 55-65°C, mechanically stir at 80-120rpm, add tetrahydrofuran, react for 5-6h, let stand for 24h, wash and dry, heat to 780-820°C in a nitrogen environment, calcine for 6-7h, and break up after cooling to obtain a low-temperature graphite negative electrode material.

2. A low-temperature graphite negative electrode material according to claim 1, characterized in that: In step A1, the usage ratio of potassium persulfate, phosphorus pentoxide, graphite flakes, concentrated sulfuric acid, sodium nitrate, potassium permanganate, hydrogen peroxide and deionized water is 2g:1g:1-2g:20-46mL:2-3.75g:20g:40-50mL:100-200mL.

3. A low-temperature graphite negative electrode material according to claim 1, characterized in that: In step A2, the usage ratio of graphite oxide, acetone, deionized water, ethanol, hydrated ammonium molybdate, and thioacetamide is 0.5-0.6 g: 280-320 mL: 50-60 mL: 50-60 mL: 0.7 g: 0.5-0.6 g.

4. A low-temperature graphite negative electrode material according to claim 1, characterized in that: In step A3, the usage ratio of epoxy resin, ethanol, MoS2-Gr and nickel oxide is 0.2-0.3 g: 20-30 mL: 1.8-2.7 g: 0.2-0.3 g.

5. A low-temperature graphite negative electrode material according to claim 1, characterized in that: In step A4, the usage ratio of ammonium persulfate, thiophene monomer, C / Ni@MoS2-Gr, and solution A is 34.0-38.0 g: 3.2-3.8 g: 0.031-0.059 g: 10-15 mL.

6. A low-temperature graphite negative electrode material according to claim 1, characterized in that: In step A5, the usage ratio of PTh@C / Ni@MoS2-Gr, N,N-dimethylformamide and tetrahydrofuran is 0.5-2g:60mL:0.8-2.4g.

7. A low-temperature graphite negative electrode material, characterized in that: The negative electrode material is prepared according to the preparation method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Lithium ion battery electrode made of graphene / MoS2 and amorphous carbon and preparation method

    CN102142538A

  • Carbon-loaded metal sulfide negative electrode material and preparation method thereof

    CN117457884A

  • Modified graphite electrode material for lithium ion battery and preparation method of modified graphite electrode material

    CN117996053A

Cited By

  • Low-temperature high-rate graphite negative electrode material and preparation method thereof

    CN120834153A

  • Low-temperature high-rate graphite negative electrode material and preparation method thereof

    CN120834153B

  • Natural graphite composite negative electrode material and preparation method and application thereof

    CN120914223A